FACTORS AFFECTING EFFECTIVENESS OF TEACHING ENGLISH FOR SPECIFIC PURPOSES IN AGRICULTURAL AND FORESTRY UNIVERSITIES IN VIETNAM - Cong Ngoc, Pham; Thi Xuan Hong, Ho (Journal of Forestry Science and Technology, 2021)
This paper analyses the effectiveness of teaching English for Specific Purposes (ESP) in several tertiary educational institutions in agricultural and forestry field in Vietnam contexts. Apart from reviewing the criteria and methods of measuring the teachers’ effectiveness including value-added models, classroom observations, manager evaluations, portfolios, self-reports of practice, and student evaluations, it also examines the challenges faced by Vietnamese university teachers in teaching ESP in agricultural and forestry field and the ways they dealt with these issues. Interviews with twenty ESP teachers who are of different levels of professional qualifications teaching different ESP major at five educational institutions in Vietnam revealed that although the teachers had different educational backgrounds, they thought they were in disadvantageous situations and conditions to teach ESP. Their levels of effectiveness were very low due to several challenges. The educational institution characteristics (the socio-cultural context) and teachers’ beliefs about teaching ESP were clearly seen as the most influential factors on their low levels of teaching effectiveness. All these factors facing the ESP teachers are regarded as the big barriers to their teaching effectiveness. This paper also presents the implications and recommendations from these findings for educational policy makers, university leaders to improve ESP teaching and learning quality in the field of agricultural and forestry in Vietnamese situations.